Pengaruh Reinforcement Guru Terhadap Kepercayaan Diri Siswa Kelas V SD Inpres 3 Wosia - Yusuf Manutede; M. M. Puji Nitis Kusumawati; Stefen Deni Besare; Like Suoth (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The study aims to determine the effect of teacher reinforcement on the self-confidence of fifth grade students of SD Inpres 3 Wosia. This research method is a quantitative type with simple regression inferential statistical analysis technique. The sample amounted to 32 people. The results showed simple linear regression inferential analysis with the equation Y = a + bX obtained the amount Y = 29.736 + 0.571X. This means that if the provision of reinforcement by teachers at SD Inpres 3 Wosia increases by 1 (one) point, then the students' self-confidence will also increase by 0.571 points. While the R2 coefficient value of 0.181 shows that the teacher's reinforcement contributes to the self-confidence of fifth grade students of SD Inpres 3 Wosia by 18.1% of the total 100%.